2004
DOI: 10.1093/aob/mch135
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Rhizobium and Arbuscular Mycorrhizal Fungi on Nitrogen and Phosphorus Accumulation by Vicia faba

Abstract: The results indicated that the synergistic or additive interactions among the components of the tripartite symbiotic association (Rhizobium-AMF-broad bean) increased plant productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
62
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(75 citation statements)
references
References 14 publications
8
62
0
5
Order By: Relevance
“…These data agreed with the previous evidence obtained from Vicia faba (Jia et al 2004), citrus (Wu and Xia 2006) and Ipomoea carnea (Amaya-Carpio et al 2009). Taking photosynthetic data herein and the above morphological data together, AM fungi substantially improved the tolerances of pigeon pea to drought stress.…”
Section: Resultssupporting
confidence: 93%
“…These data agreed with the previous evidence obtained from Vicia faba (Jia et al 2004), citrus (Wu and Xia 2006) and Ipomoea carnea (Amaya-Carpio et al 2009). Taking photosynthetic data herein and the above morphological data together, AM fungi substantially improved the tolerances of pigeon pea to drought stress.…”
Section: Resultssupporting
confidence: 93%
“…An increase of parameters that quantified the N 2 -fixing organ -nodule number and dry weight, as well as specific ARA activity with an increase of P applied was observed also in common bean by Olivera et al (2004). Jia et al (2004) reported that inoculation with AM fungi promoted biomass production and photosynthetic rates in Vicia faba because of the enhanced P supply due to AM fungi inoculation. Some authors (Saxena et al 1997) reported that tripartite symbiosis be- Values are means ± SE, n = 3; different letters indicate significant differences assessed by Fisher LSD test (P ≤ 0.05) after performing ANOVA multifactor analysis tween green gram, Bradyrhizobium japonicum and several AM fungi cultures increased the growth, nodulation and ARA to varying levels for almost all pairs.…”
Section: Resultsmentioning
confidence: 74%
“…Similar positive effects of AMF on nutrient uptake in legumes were reported earlier (Zaidi et al 2003, Ilbas and Sahin 2005, Lin et al 2007). The higher P, K, Mg, Fe, Mn, Zn and Cu uptake of the mycorrhizal chickpea plants in parallel with the lack of difference in N uptake of mycorrhizal and non-mycorrhizal plants in a growth substrate with adequate N levels might indicate a positive effect of AMF on dry matter by increasing the uptake of nutrients other than N (Jia et al 2004). Our results are in accordance with those of previous work on chickpea by Akhtar and Siddiqui (2007) showing no effect on N uptake but increased P and K uptake in mycorrhizal plants.…”
Section: Discussionmentioning
confidence: 99%
“…Growth and N acquisition of mycorrhizal plants benefit from N fertilization depending on the N availability from the soil (Jia et al 2004, Azcón et al 2008). In addition, there is evidence that genetic variability in the fungal partner influences N acquisition (Vázquez et al 2001).…”
mentioning
confidence: 99%